Analytical cognitive style moderation on promotion and turnover intention - Abdul Halim, Busari; Yasir Hayat, Mughal; Sajjad, Nawaz Khan; Shahid, Rasool; Asif Ayub, Kiyani (Emerald Publishing Limited, 2017)
Purpose – This paper argues that teachers’ promotion should also have an impact on turnover intention. The purpose of this paper is to determine the relationship between promotion and turnover intention of advance learning institutions of the Khyber Pakhtoon Khwa Province of Pakistan and the moderating effect of the analytical cognitive style. Design/methodology/approach – A quantitative approach is used predominantly. A questionnaire survey research design is used to collect the data from the entire province and 502 completed questionnaires were collected from the respondents. The questionnaire included the Job Descriptive Index consisting of seven items on job satisfaction, the turnover intention questionnaire consisting of three items and a five-point Likert scale used to determine cognitive style index (CSI); the CSI was used. The fourth section included an open-ended questionnaire and the fifth section included demographic variables. Hierarchical multiple regressions were used to check how much variance promotion occurs upon turnover intention and it also determined how much variance analysis cognitive style occurs upon promotion and turnover intention of advance learning institutions of the KPK province of Pakistan. The correlation results from a bivariate Pearson correlation showed significant results, which were later strengthened by the regression results. Findings – The findings suggested that a negative relationship was found between promotion and turnover intention, whereas a weak correlation was found between promotion and analytical. Moderating results show that analytical cognitive style does act as a moderator between the promotion and turnover intention. Research limitations/implications – This research was only carried out on advance learning institutions; thus, the findings can only be generalized to higher education institutions in the Khyber Pakhtoon Khwa state. Practical implications – This extended model of job satisfaction will be useful to lead to changes in job satisfaction and turnover intention of academicians of the Khyber Pakhtoon Khwa province of Pakistan. The findings of this study could be used to guide the management of advance learning institutions and professional academicians to build targeted learning activities around key components of the academician’s promotion, determine where individuals are in their journey, set personalized goals and provide feedback to the management in the process of the development of policies for academicians of advance learning institutions. Social implications – The findings of this study will help the higher education commission of Pakistan to make policies that will enable higher education institutions to formulate flexible promotion policies for teachers in order to retain them. Originality/value – The findings of this study are a valuable extension of the relevant research as this is the first empirical study to examine the effects of cognitive style on promotion policies and turnover intention in advance learning institutions of Pakistan. In the context of an efficient and effective educational policy, a greater understanding of an academician’s promotion could facilitate the development of a more effective policy practice that would increase not only the job satisfaction of the academicians but decrease the turnover intention of the academicians.